Strategi Pemerintah Daerah untuk Meningkatan Produksi Jagung di Nagari Pinagar Aur Kuning - Taufik Maulana; Ali Rahman (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to identify the local government’s strategies for increasing corn production in Nagari Pinagar Aur Kuning, Pasaman Subdistrict, West Pasaman Regency. The background of this study is based on the fact that corn yields remain low despite the availability of extensive land, as well as farmers’ limited understanding of seed selection and proper fertilization techniques. The research design employed was a descriptive study using a qualitative approach. The data consisted of primary data obtained through interviews and direct observations with corn farmers and village government officials, as well as secondary data derived from literature, documents, and previous studies. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the local government’s strategy to increase corn production involves providing high-yielding seeds, subsidized fertilizers, agricultural tools and machinery, agricultural infrastructure development, and extension services to farmers. However, the implementation of these strategies has not been fully optimal due to various constraints, such as farmers’ low level of knowledge, limited mastery of technology, pest and disease infestations, and unpredictable weather conditions. From an Islamic economic perspective, corn production has reflected values such as hard work and the optimal use of resources. However, aspects of sustainability and the common good still need to be improved. Therefore, stronger synergy between the government and farmers is needed through enhanced training.